Exploring Strategies of Teaching Speaking Skills for Hotel Staffs (A Literature Review) - Nyoman Canestra Adi Putra (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The Central Statistics Agency of Indonesia recorded that the number of foreign tourist visits to Indonesia in 2022 reached 5.47 million visits. It means that tourism sector in Indonesia must be ready to accommodate tourists visiting the country by providing excellent service. Communication promotes positive engagement between the hospitality industry staffs and the guests. However, many hotel staffs cannot use English effectively due to many factors, such as lack of vocabulary, improper grammar, fears of mistakes and anxiety. Therefore, speaking skill enhancement is needed through effective teaching strategies. This study aimed at exploring and identifying effective teaching strategies to improve the staffs’ speaking skill. The study used literature review method, which summarizes and evaluates a body of writings about a specific topic (Knopf, 2006). Based on the literature review, there are five main effective strategies in teaching speaking skill for hotel staffs; they are role play, discussion, picture describing, storytelling and interview. It is suggested that teachers can use these strategies to maximize hotel staffs’ speaking skill.